Tecnologia educativa musical para aprendizagem da fisiologia da lactação: tradução do conhecimento - Cherubim, Daiani Oliveira (2018)
Educational technologies are innovative devices for the teaching-learning process. The use of the musical language facilitates the understanding of the knowledge making the participant educando in this process, being useful in the professional formation. Among the themes, the process of physiology of lactation is highlighted as an important content for clinical practice, since breastfeeding offers numerous benefits for maternal and child health. Thus, we have as a general objective: to construct and validate an educational technology about the physiology of lactation for teaching-learning in professional training in health. As specific objectives: create a composition (letter and melody) about the content of the physiology of lactation and apply it to the validation of experts in the topic of breastfeeding. Method: Methodological study, with a quantitative approach, based on the cyclical movements of the theoretical reference of the Translation of Knowledge. In the first phase was carried out the in-depth reading of literature on the subject. Afterwards, key points about the physiology of lactation were written, to compose the lyrics of the song. As a product of the third phase, the melody of educational technology was developed to be used in didactic activities with undergraduate students. The validation period for content by judges was from September to December 2017. Results: for the validation of content of the educational technology, 18 judges were approved for breastfeeding experts. These were selected on the websites of the International Baby Food Action Network-Brazil and Brazilian consultants registered with the International Board Certified Lactation Consultant. The technology has been validated with the Global Content Validity Index of 0.89. Some suggestions were important for the improvement of the technology. Final Thoughts: Musical Educational Technology can be useful in the teaching-learning process of lactation physiology, making this process pleasurable and meaningful, implying positively the social use of knowledge for the transformation of reality into professional training.